Association between Serum Leptin Levels in Obesity and Type 2 Diabetes Mellitus - Raviraj Gawali; Arun Bahulikar; Deepak Sadashiv Phalgune; Ajit Tambolkar (Journal of Clinical and Diagnostic Research, 2019)
Introduction: It is hypothesised that leptin, the gene product of the obese gene plays an important role in regulating body weight and has a potential role as a treatment tool for obesity and Type 2 Diabetes Mellitus (T2DM). There is little documentation describing the relationship between serum leptin and the indices of obesity such as Body Mass Index (BMI) and T2DM. Aim: To determine the relationship of serum leptin levels with BMI and type 2 DM patients. Materials and Methods: This observational study was conducted in 140 patients with known diagnosis of type 2 DM with and without obesity and non-diabetic patient with BMI ≥25 kg/m2 . Patient’s BMI and waist hip ratio were noted. Estimation of fasting serum leptin, fasting serum glucose, serum Total Cholesterol (TC), serum Triglycerides (TG), serum High Density Lipoprotein (HDL) cholesterol, serum Low-Density Lipoprotein (LDL) cholesterol and Very Low Density Lipoprotein (VLDL) cholesterol were done. Kruskal Wallis test and MannWhitney U test was used to compare median of continuous variables. Correlation analysis was done using Spearman’s correlation technique. Results: Median serum leptin level was significantly higher in patients who had DM and whose BMI was ≥25 kg/m2 . Fasting glucose, TC, LDL cholesterol, and VLDL cholesterol showed statistically significant and positive correlation, whereas HDL-cholesterol showed statistically significant and negative correlation with serum leptin levels. Conclusion: Serum leptin levels were higher in type 2 DM and obese patients. Fasting glucose, TC, LDL cholesterol, and VLDL cholesterol showed positive correlation, whereas HDL-cholesterol showed negative correlation with serum leptin levels.